The effect of wellbore scaling on exergy in geothermal fluid : a computational fluid dynamic wellbore model estimate - Ilham Narendrodhipo 1995- (2021)
Calcite scaling is a typical scaling problem that occurs in geothermal wells because of the flash boiling phenomenon. Studies related to geothermal scaling show that scaling affects output productivity adversely. In this thesis, two-phase modelling and an exergy analysis were performed to learn the mechanism of the pressure drop and exergy changes due to calcite scaling in the geothermal well. The work, therefore, provides a method to model the two-phase flow in the geothermal wellbore dealing with calcite scaling and exergy calculation within it. This study pertains to one of the wells in Svartsengi, Iceland. The scaling of the well has a thickness ranging up to 2 inches for a length of 100 meters in the borehole. By applying the two-phase modelling on wellbore fluid flow using the computational fluid dynamic method (ANSYS Fluent), this work allows an estimate of how the fluid thermodynamic properties change. The Eulerian model will be employed in this computational fluid dynamic study. Furthermore, the user-defined function code is integrated with the solver in order to analyse the exergy changes occurring due to scaling. The entropy and enthalpy properties are derived from empirical corelation form NIST data in which based on temperature and pressure to calculate exergy term. The pressure result from the computational fluid dynamic modelling by Vijay Chauhan shows satisfaction with the pressure log data. The pressure loss within the domain is approximately accounted for 7 bars. Furthermore, the user-defined code result shows that entropy within the domain increases from 2.7100 kJ/kg K at the inlet to 2.7178 kJ/kg K at the outlet. It also shows that the specific exergy in the inlet is started at 250.5 kJ/kg and reduced by 3 kJ/kg. The highest rate of exergy reduction in the domain is found out to be in the point where the fluid flow passes through the calcite zone in which calcite scaling contributes 30% exergy reduction. It can be concluded that the pressure decrease, entropy increases, and exergy decrease ...